Co-national and transnational networks in international migration to Spain - Nina Neubecker; Marcel Smolka (University of Tübingen, Faculty of Economics and Social Sciences, 2012)
This paper provides evidence that transnational networks, defined as networks operating across nationalities, are shaping observed patterns of international migration. In a stylized model of migration with random friendship formation, individuals from a given origin country are attracted to destinations hosting large migrant communities from countries which are culturally and geographically close to their own origin country. In addition, the attracting force of a large community of co-national migrants is the larger, the larger the community of migrants from other culturally proximate countries in the same destination. Both predictions are supported by aggregate migration data on international migration to Spain, detailed by origin country and destination province. Our findings imply that the literature estimating network effects in migration has been overly restrictive in its definition of migrant networks.
urn:nbn:de:bsz:21-opus-64834
Keywords: F22; 330; International migration; Co-national and transnational friendships; Network effect; Spain; Internationale Wanderung; Soziales Netzwerk; Kulturelle Identität; Entfernung; Spanien